THE DEVELOPMENT OF KIDOLAND TOURISM OBJECT IN PLESAN VILLAGE, NGUTER DISTRICT, SUKOHARJO DISTRICT - Ni'mah, Uwatun; Rahman, MS Khabibur; Rahmawati, Talitha (Journal of Geography Science and Education, 2021)
This research aims to: (1) analyze  the tourism potential in Kidoland tourism objects, (2)  investigate the changes in the tourism potential of Kidoland tourism objects after the development with a master plan.This study uses a qualitative descriptive method, which describes and describes tourism potential, as well as a SWOT analysis to determine the development strategy of tourism objects with a master plan design to determine changes in tourism potential. The data collection technique used was through field observations and documentation. Data analysis techniques are scoring and descriptive. The results of this study are: (1) The potential of the Kidoland tourism object in the observation, the value of 17.8 is obtained. Where the value of 17.8 is obtained from the per-variable calculation, namely the attractiveness with a value of 10, accessibility 3.6, and basic infrastructure and facilities with a value of 4.2. (2) To increase the tourism potential of Kidoland tourism objects, an object development plan is carried out with a master plan, namely the addition of facilities and infrastructure to the object, namely the addition of toilets, worship facilities, gazebo, electricity expansion and a garden. From the design of the master plan there is an increase in potential with numbers2.1. The initial potential with a total value of 17.8 becomes 19.9.